Reinforced Concrete Fracture Diagnostics under Conditions of Bending by Parameters of the Electric Response to an Impact Action; Technical Physics; Vol. 64, iss. 1 - Fursa T. V. Tatyana Viktorovna; Dann D. D. Denis Dmitrievich; Petrov M. V. Maksim Vyacheslavovich; Sokolovsky A. N. Aleksey Nikolaevich (2019, 2019)
Title screen